Constructing a zwitterionic ultrafiltration membrane surface via multisite anchorage for superior long-term antifouling properties1. Issue 50 (4th June 2015) - Zhu, Junao; Su, Yanlei; Zhao, Xueting; Li, Yafei; Zhang, Runnan; Fan, Xiaochen; Ma, Yanyan; Liu, Yuan; Jiang, Zhongyi
<x xml:space="preserve">Abstract</x> A novel zwitterionic membrane surface was constructed which exhibited stable antifouling ability by the formation of multisite anchorage covalent bonds.